1997
DOI: 10.1021/jo961921o
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Pyridinolysis of Alkyl Aryl Thionocarbonates

Abstract: The reactions of methyl 4-nitrophenyl, ethyl 4-nitrophenyl, and ethyl 2,4-dinitrophenyl thionocarbonates (MNPTOC, ENPTOC, and EDNPTOC, respectively) with a series of 3- and 4-substituted pyridines are subjected to a kinetic investigation in water, 25.0 degrees C, ionic strength 0.2 M (maintained with KCl). Under amine excess, pseudo-first-order rate coefficients (k(obsd)) are obtained, which are linearly proportional to the free-pyridine concentration. The second-order rate coefficients (k(N)) are obtained as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
101
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(120 citation statements)
references
References 53 publications
19
101
0
Order By: Relevance
“…The reactions of pyridines and SA amines with O ‐ethyl O ‐(2,4‐dinitrophenyl) thionocarbonate in aqueous solution proceed by attack at the thiocarbonyl carbon exclusively49. No products derived from attack at the C‐1 aromatic carbon were found50.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions of pyridines and SA amines with O ‐ethyl O ‐(2,4‐dinitrophenyl) thionocarbonate in aqueous solution proceed by attack at the thiocarbonyl carbon exclusively49. No products derived from attack at the C‐1 aromatic carbon were found50.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not so surprising since such a large β nuc value for the reactions with pyridines has often been observed for pyridinolyses of various esters, e.g., 3-nitrophenyl 4methyl thionocarbonate (βnuc = 1.2), 10 bis(4-nitrophenyl) thionocarbonate (βnuc = 1.0), 11 alkyl aryl thionocarbonate (βnuc = 1.0). 19 Therefore, it appears to be common that the positive charge developed at the nitrogen atom of the transition-state would be more significant for the reactions with the pyridines than for those with the primary and secondary amines.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the center of the Brønsted curvature for the thiocarbonyl series, II, shifted to a lower pK a value, i.e., from pK a Њ ≥ pK a = 9.51 (for p-MeO-benzylamine in H 2 O) for the carbonyl to pK a Њ ≤ pK a = 9.14 (for p-Cl-benzylamine in H 2 O) for the thiocarbonyl series. The smaller pK a Њ value results from a smaller k Ϫa /k b ratio (for a given amine and leaving group) 11 for the thiocarbonyl compared to the carbonyl compound. It has been shown that the change of carbonyl to thiocarbonyl decreases both k Ϫa and k b but the decrease in k Ϫa is greater.…”
Section: Rate = K Obs [S]mentioning
confidence: 99%